Habib Ja'far's Construction of Moderate Islam in Youtube Podcast #LogIndiCloseTheDoor: A Critical Discourse Analysis Study - Agripina, Annisa; Abrian, Rizky (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Religious moderation is an agreement that is expected to balance people's religious life, in accordance with the diversity framework that applies in Indonesia. Every religion certainly teaches the values ​​of goodness, peace and tolerance to its followers. As is the case in the Islamic religion which teaches the noble value of religious moderation, as stated in the holy book Al-Qur'an in the term wasathiyah which means the middle way. The concept of wasathiyah is a balance between strong beliefs and tolerance. This research aims to analyze the dialogue conducted by Habib Husein Ja'far with Onadio Leonardo on the #LogIndiCloseTheDoor. Podcast content based on the words of Allah SWT in Surah An-Nahl verse 125 in the context of religious moderation. Carried out using a qualitative descriptive analysis method with data collection techniques in the form of documentation. The urgency of this research is to find out Habib Husein Ja'far's method of preaching. The results of the research show that in his preaching he represents Islam as a religion that is rahmatan lil alamin in accordance with the four indicators of religious moderation that are used as a basis in Indonesia. These indicators include tolerance, non-violence and national commitment.